First record of Melampodium divaricatum (Asteraceae) in West Tropical Africa. (16th April 2019) - Adegbite, Adegoke Emmanuel; Ojo, Funmilola Mabel; Abraham, Olubukola Grace; Francis, Joseph; Balogun, Sunday
Abstract : A plant that showed morphological closeness to Aspilia africana (Pers) C. D. Adams (Asteraceae) was spotted and collected in 2015 along Afe Babalola University road, Ado‐Ekiti, Ekiti State, Nigeria with coordinates 7°36′59.99″N, 5°12′60.00″E. However, upon closer observation some distinct and peculiar characteristics that clearly distinguished it from Aspilia africana were revealed, e.g. sterility of the disc florets and production of achenes by ray florets only. Another striking character of the plant was total emptying of the capitulum after achene maturation, leaving an empty capitulum cup on the plant. Literature and herbarium searches revealed that the plant had neither been reported from West Tropical Africa nor collected in any herbarium in Nigeria before. The plant was eventually identified as Melampodium divaricatum (L.) which is an annual erect herb, distributed in tropical and subtropical regions but mostly restricted to Mexico, North America and Central America. Morphological, reproductive and cytological studies carried out on the plant revealed it to possess a highly branched erect pigmented stem, simple opposite sub sessile leaves with acute apex and distantly serrated margins, capitula with yellow unisexual disc and ray florets, sterile disc florets, fertile ray florets, relatively high pollen fertility (92.85%), a somatic chromosome number of 2n = 24 and regular formation of 12 bivalents, indicating the plant to be a diploid species. Further studies on Melampodium in Nigeria and a general revision of the flora of West Tropical Africa is suggested as well as the need to monitor M. divaricatum in the region since it appears to have the capacity to become invasive.